Application Of The Demonstration Method To Improve Student Learning Outcomes In Mathematics Learning In Class IV SD Negeri 1 Ngrakum - Lis Setyaningrum (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
Application of the Demonstration Method to Improve Student Learning Outcomes in Learning Mathematics in Grade IV SD Negeri 1 Ngrakum, Kemusu, Boyolali. This study aims to improve learning outcomes through demonstration methods in learning Mathematics for students at SD Negeri 1 Ngrakum, Kemusu. This study used the recipient of the action as a subject, namely fourth grade students at SD Negeri 1 Ngrakum, totaling 4 students. The research object is to improve mathematics learning outcomes by applying the demonstration method. Data collection techniques used are observation, tests, questionnaires, and documentation.Based on the results of research and discussion, the following conclusions can be drawn. Learning by applying the demonstration method can improve the mathematics learning outcomes of fourth grade students at SD Negeri 1 Ngrakum. The average Mathematics learning outcomes at the pre-action stage showed a value below the KKM, namely 57.50, then increased from 23.75 to 81.25 in cycle II. Classical learning completion (≥ KKM) at the pre-action stage is included in the very poor category, namely 25%, increasing by 75% to 100% in cycle II stage. The conclusion from this classroom action research is that the application of the demonstration method can improve the learning outcomes of fourth grade students at SD Negeri 1 Ngrakum, Kemusu